(untitled) (Scientific journal of the Fergana State University, 2024)
Currently, highly talented, intelligent, creative young people are recognized and valued, which is clearly reflected in the policy of our state. Therefore, the urgent need is to increase the creative abilities of young people, who are our future heirs, and their maximum realization. This article describes how the Prophet Muhammad in his hadiths glorified those who acquired knowledge and sought to do good, and also describes the valuable thoughts of Central Asian thinkers on the problems of creativity and intellectual development, like Al-Fergani, Al - Kindi, Farabi, Beruni, Ibn Sina and Alisher Navai.